CYBER SOVEREIGNTY AND CYBERCRIME REGULATION: A COMPARATIVE STUDY OF INDONESIA’S ITE LAW AND MALAYSIA’S COMPUTER CRIMES ACT - A.Haidar Muhammad Bagir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Based on a comparative analysis of the development of cybercrime regulations in Indonesia and Malaysia, it can be concluded that both countries recognize the urgency of strengthening cyber sovereignty as part of protecting national interests in the digital era. However, the normative and philosophical approaches used show quite fundamental differences. Indonesia, through the 2008 Electronic Information and Transactions (ITE) Law, its 2016 revision, and the second amendment in 2024 (Law No. 1 of 2024), developed a broad and comprehensive regulatory model. These regulations not only regulate technical acts of cybercrime such as illegal access and data manipulation, but also encompass dimensions of digital content, including insults, hate speech, and the distribution of prohibited information. The 2024 revision demonstrates the country's efforts to clarify norms, align with the new Criminal Code, and respond to developments in digital technology. However, the main challenges remain: consistent law enforcement, the potential for multiple interpretations of norms, and the need to improve the capacity of law enforcement officers. In contrast, Malaysia, through the Computer Crimes Act 1997 (Act 563), initially adopted a more technical and limited approach, focusing on illegal access and misuse of computer systems. However, recent developments through the Cyber Security Act 2024 indicate a paradigm shift toward a more structural and risk-management-based approach, particularly in protecting the nation's critical information infrastructure. These reforms demonstrate Malaysia's focus on strengthening cybersecurity systems and risk governance, rather than solely criminalizing digital content.Keywords: Cybercrime, Indonesia, Malaysia.